Symmetric Energy-Conserved Splitting FDTD Scheme for the Maxwell's Equations (Communications in Computational Physics, 2009)
In this paper, a new symmetric energy-conserved splitting FDTD scheme(symmetric EC-S-FDTD) for Maxwell's equations is proposed. The new algorithm inheritsthe same properties of our previous EC-S-FDTDI and EC-S-FDTDII algorithms:energy-conservation, unconditional stability and computational efficiency. It keeps thesame computational complexity as the EC-S-FDTDI scheme and is of second-order accuracyin both time and space as the EC-S-FDTDII scheme. The convergence and errorestimate of the symmetric EC-S-FDTD scheme are proved rigorously by the energymethod and are confirmed by numerical experiments.